Impact of HIV infection on tuberculous pleural effusion. (April 2016) - Marjani, Majid; Yousefzadeh, Amir; Baghaei, Parvaneh; Tabarsi, Payam; Moniri, Afshin; Masjedi, Mohammad Reza; Velayati, Ali Akbar
The nature of tuberculosis (TB), being one of the most common opportunistic infections, is different among HIV-infected patients than HIV-negative patients. A retrospective study was conducted on HIV-positive and HIV-negative patients with new TB pleural effusion who were admitted to the National Research Institute of Tuberculosis and Lung Diseases in Tehran, Iran from 2005 to 2012. The two groups were compared with respect to clinical, imaging, mycobacteriologic and histopathologic characteristics of TB pleural effusion. In all, 42 HIV-positive and 132 HIV-negative cases of TB pleural effusion were included. Bilateral pleural effusion was statistically more common in the HIV-positive group ( p  = 0.004, OR = 3.81, 95% CI: 1.46–9.94) without any correlation with CD4 cell count. Pulmonary infiltration was found in 81% of HIV-positive and 49.2% of HIV-negative patients ( p  = 0.001, OR = 4.38, 95% CI: 1.88–10.1). Mycobacteriologic studies led to the diagnosis of TB in 66.6% of HIV-infected and 49.2% of HIV-negative patients. In 23.8% of HIV-positive and 50.7% of HIV-negative patients TB was ultimately diagnosed by pleural biopsy. HIV remained significantly associated with positive culture of pleural fluid in multivariate analysis. The diagnostic approach to TB pleural effusion in HIV-infected patients may be different. The diagnostic yield of mycobacteriologic studies was higher among HIV-positive patients, which may help in reducing the need for invasive procedures like pleural biopsy.